Topology Optimization for Air-Side Cooling Channel Flow and Heat Transfer in Panel Type Radiator - Zexuan Huang; Wenrong Si; Chenzhao Fu; Yue Tian; Peng Yuan; Jian Yang; Qiuwang Wang (Chemical Engineering Transactions)
To address the internal overheating issues caused by increased capacity in oil-immersed transformers, this paper presents the design of a novel panel-type radiator. Based on the traditional bottom-blow air-cooled panel-type radiator, this design incorporates side baffles to prevent lateral airflow leakage and adds metal fins on the panel surface to enhance thermal performance. Employing a variable-density topology optimization approach, the fin distribution in a 2D channel model is optimized. A multi-objective function obj1 containing a weight adjustment factor ? and a single-objective function obj2 introducing a performance evaluation factor PEC are proposed. The effect of ? variation on the fin distribution over a non-uniform thermal surface is analysed, and the topological differences under different objective functions are compared. The optimization results are validated through three-dimensional simulation, indicating that the channel optimized with obj2 outperforms channels with obj1 in both flow and heat transfer performance. Compared to the optimal case of obj1, the comprehensive heat transfer performance PEC of the obj2 condition improved by 11 %-15 %, with the maximum PEC value reaching 1.35.